The Career of a Canadian Trade Union Leader: C.H. Millard 1937-1946 - Macdowell, Laurel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
In Canadian political history, the primary focus of historians has been on leading politicians. Trade union leaders have been virtually ignored. This paper partly fills this gap in presenting the career of C.H. Millard.